2020
DOI: 10.1007/s43153-020-00073-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of diethyl carbonate from ethanol and CO2 over ZrO2 catalysts

Abstract: Diethyl carbonate (DEC) is a versatile chemical with several commercial uses. The synthesis of DEC from carbon dioxide and ethanol is both environmentally friendly and can be integrated into the ethanol biorefinery. A thermodynamic evaluation was made to predict the amount of DEC produced at equilibrium at the reaction conditions used in this work. Zirconium oxide solids were prepared using sol-gel methodology and were loaded with Na, Mg or PO 4 −3 using the incipient wetness impregnation method. Catalytic tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…As shown in Figure , the main catalysts were CeO 2 , ZrO 2 , and supported catalysts. To research a new preparation method to obtain the desired structure of CeO 2 or ZrO 2 , the DEC yield was slightly improved.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure , the main catalysts were CeO 2 , ZrO 2 , and supported catalysts. To research a new preparation method to obtain the desired structure of CeO 2 or ZrO 2 , the DEC yield was slightly improved.…”
Section: Introductionmentioning
confidence: 92%
“…Literature reported for the DEC synthesis reaction from CO 2 and ethanol without third additives from 2015 to the present. …”
Section: Introductionmentioning
confidence: 99%
“…From these recent references, it was found that ethanol conversion and DEC yield remained at a low level. The best DEC yield was reported in reference 20 published in 2021. Nevertheless, 2-cyanopyridine was used in this DEC synthesis reaction.…”
Section: Introductionmentioning
confidence: 95%
“…There are many third monomer candidates, and the best one among them is 2-cyanopyridine. 31 However, 2-cyanopyridine is more expensive than DEC and its consumption rate is also very high. 32 As such, it is not economical to use 2-cyanopyridine for the commercial production of DEC. At present, the main challenge of the synthetic route using CO 2 and ethanol is the low DEC yield.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, the synthetic conditions can be generally divided into two groups, with or without a third monomer. 8–31 A third monomer can help improve the yield of DEC. Without a third monomer, the ethanol conversion rate is usually very low, ranging from ca.…”
Section: Introductionmentioning
confidence: 99%